2016
DOI: 10.2298/gensr1601373p
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of drought and salt stress effects on germination and seedling growth of pea

Abstract: Seed germination is first critical and the most sensitive stage in the life cycle of plants compromise the seedlings establishment. Salt and drought tolerance testing in initial stages of plant development is of vital importance, because the seed with more rapid germination under salt or water deficit conditions may be expected to achieve a rapid seedling establishment, resulting in higher yields. The aim of this study was to determine whether the pea seed germination and seedling growth were inhibited by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 17 publications
6
44
1
1
Order By: Relevance
“…There may be differences between the results obtained from the germination test under laboratory conditions and the results obtained from field conditions. In a study, it was stated that post-germination stage are more sensitive than germination stage in pea under salt and drought stress (Petrović et al, 2016). In addition, Noreen et al (2007) showed that although significant variations in germination of pea varieties under salt stress conditions, an evaluation was not sufficient according to germination results in tolerance to salinity.…”
Section: Figure 9 Effect Of Salt Stress On Pv In Chickpea Cultivarsmentioning
confidence: 99%
“…There may be differences between the results obtained from the germination test under laboratory conditions and the results obtained from field conditions. In a study, it was stated that post-germination stage are more sensitive than germination stage in pea under salt and drought stress (Petrović et al, 2016). In addition, Noreen et al (2007) showed that although significant variations in germination of pea varieties under salt stress conditions, an evaluation was not sufficient according to germination results in tolerance to salinity.…”
Section: Figure 9 Effect Of Salt Stress On Pv In Chickpea Cultivarsmentioning
confidence: 99%
“…Hasil tersebut menunjukkan bahwa hambatan pertumbuhan tetap berlanjut hingga tanaman pindah lapang. Munns dan Tester (2008) dalam Petrovic et al (2016) m e n y a t a k a n b a h w a h a m b a t a n pertumbuhan akibat akumulasi garam pada awal perkembangan seedling adalah konsekuensi sebagai akibat potensial osmotik yang diinduksi oleh kadar garam. Pada tahap selanjutnya, pengaruh toksik + dari ion Na yang terakumulasi pada organ daun juga menjadi faktor yang akan menghambat pertumbuhan tanaman selanjutnya.…”
Section: Stem Diameter (Mm)unclassified
“…Drought is a multifaceted stress condition that causes serious yield limitations depending on plant growth stage, stress duration, and severity MUSCOLO et al, 2014). Drought tolerance testing in initial stages of plant development is of a vital importance, because the seed with more rapid germination under water deficit conditions may be expected to achieve a rapid seedling establishment, resulting in higher yields (PETROVIĆ et al, 2016). Polyethylene glycol (PEG) is widely used to simulate drought conditions.…”
Section: Introductionmentioning
confidence: 99%
“…PEG is an inert osmotic agent whose molecules are too large to penetrate into seed, thus preventing any toxic effects. It does not enter the apoplast, so water is withdrawn not only from the cell but also from the cell wall (PETROVIĆ et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation